پەیوەندى واتایى نێوان کار و بەشەکانى ترى ڕستە - فرهادى, ساجدە عبداللە (Sulaimani Journal for Humanities, 2002)
There is no denying that the relationships between the verb and the other elements of the sentence determine its grammaticality or acceptability. These relations can be either semantic or syntactic in nature. This paper is concerned with the semantic ties which link together the various elements of a sentence, with-in the framework of the dependency theory, which holds that the verb is the 'center' or the ‘selector' that imposes its own features upon the selected', be it the subject, object or modifiers, and adjuncts. The data on which the study is based are from Central Kurdish. They are naturally occurring utterances or sentences from literary books. The paper comprises two sections a part from an introduction and some concluding remarks. The first section is a critical study of the previous works in Kurdish that are related to the topic. The second section includes the following sub- heads: the paradigmatic and syntagmatic semantic relations, collocational constraints, selectional restrictions, semantic abnormality and types of semantic abnormality: semantic clash and semantic redundancy.